P-006 Angiographic and clinical outcomes after endovascular therapy for acute ischemic stroke due to vertebrobasilar occlusions: pooled analysis of the Merci Registry, MERCI, and multi MERCI trials. (4th July 2012) - Nogueira, R; Jovin, T; Smith, W; Rymer, M; Liebeskind, D; Budzik, R; Devlin, T; Walker, G; Lutsep, H
Abstract : Objective: To describe the results of endovascular thrombectomy in a large prospective cohort of Acute Basilar Artery Occlusion (BAO) patients. Background: BAO is a serious but uncommon condition accounting for only 6%–10% of large-vessel strokes. Design/Methods: Our cohort included all BAO patients from three different prospective thrombectomy studies - the MERCI trial, the Multi MERCI trial, and the MERCI Registry. Successful recanalization was defined as TIMI 2–3 in the Merci/Multi-Merci trials and TICI 2–3 in the Merci Registry. Good Outcomes was defined as 90-day mRS 2. Results: Ninety-nine patients were identified (mean age, 61.6±15 years (range, 31–93); male gender, 70.7%; mean baseline NIHSS, 20.5±9.4 (median, 19); baseline mRS0-1, 95.9%). Fourteen patients (14.1%) received pre-procedure IV rt-PA. The mean time-from-symptom-onset (TSO) to arterial puncture was 9.23±12.45 h (median, 6.15) with 34.1% of patients treated >8 h. All patients were treated with at least one pass of Merci (average, 2.3±1.6). Other treatments included: intra-arterial rt-PA/urokinase (53.5%), proximal angioplasty (22.1%, 19/86) or stenting (14.0%, 12/86), Penumbra (15.3%, 11/72), and other mechanical (29.1%, 25/86). Successful recanalization was achieved in 88.9% (88/99). The overall mean (median) NIHSS dropped from 20.5±9.4/19 on admission to 13.4±14.5/6 on discharge. The overall rate of good outcomes was 31.6% (31/98). 90-day mortality was 38.8% (38/98). The SICH rate was 8.9% (7/79). The rate of good outcome was numerically higher (34.5% vs 9.1%) and mortality was numerically lower (36.8% vs 54.5%) in the revascularized vs non-revascularized patients. Notably, only one of 31 (3.2%) patients achieved a good outcome in the absence of recanalization. Patients with good outcome had significantly lower age (56.6 vs 63.6), baseline NIHSS (14.86 vs 23.15), and hypertension (51.6% vs 73.1%) but higher baseline functional status (mRS 0–1, 100% vs 93.8%) as compared to patients with bad outcomes. However, there was no difference in terms of TSO to puncture (9±13 vs 9±13 h), glucose levels (130±27 vs 152±62 mg/gl), intubation (82.6% vs 90.4%), or treatment modalities between these two groups. Conclusions: Mechanical thrombectomy in BAO appears to be associated higher recanalization rates than previous reports of intravenous or intra-arterial thrombolysis. In concordance to previous studies, the chances of good outcomes are dismal in the absence of recanalization. Competing interests: R Nogueira: Concentric Medical, Inc., ev3 neurovascular, Coaxia, Rapid Medical. T Jovin: Concentric Medical; ev3 neurovascular; Coaxia. W Smith: Concentric Medical. M Rymer: Genetech. D Liebeskind: Concentric Medical; Coaxia. R Budzik: Concentric Medical. T Devlin: None. G Walker: Concentric Medical, Inc. H Lutsep: Concentric Medical.